Checklist inspections and modifications: applying Bloom's taxonomy to categorise developer comprehension - McMeekin, D.; Von Konsky, Brian; Chang, Elizabeth; Cooper, David (IEEE Computer Society, 2008)
Software maintenance can consume up to 70% of the effort spent on a software project, with more than half of this devoted to understanding the system. Performing a software inspection is expected to contribute to comprehensionof the software. The question is: at what cognition levels do novice developers operate during a Checklist-Based code inspection followed by a code modification? This paper reports on a pilot study of Bloom's taxonomy levels observed during a Checklist-Based inspection and while adding new functionality unrelated to the defects detected. Bloom's taxonomy was used to categorise think-aloud data recorded while performing these activities. Results show the Checklist-Based Reading technique facilitates inspectors to function at the highest cognitive level within the taxonomy and indicates that using inspections with novice developers to improve cognition and understanding may assist integrating developers into existing project teams.